Is it still necessary to roughen the Y-TZP surface? - Bastos, Natália Almeida (2017)
Statement of the problem. The yttria-stabilized tetragonal zirconia (Y-TZP) ceramics are widely used manufacturing of dental prostheses. Since it is most used as framework, the ceramics veneers still show fractures, resulting in reduction of longevity of the prosthesis. Objective. Evaluate and test the effectiveness of roughening treatments between Y-TZP and veneering ceramic before liner application. Material and methods. Forty Y-TZP discs (12.5mm Ø and 3.5mm thickness) were divided in four groups (n = 10): LC: application of the proprietary liner only; S40: pre-sintered sonication with 40 % nominal power for 15 minutes; S70: pre-sintered sonication with 70 % nominal power for 15 minutes; JOX: sandblasting with 50 m aluminum particles. After roughening treatments, the liner was applied to the surface of the samples in all groups. After sintering, the specimens were subjected to confocal laser scanning microscopy (CLSM) and atomic force microscopy (AFM) analyses to evaluate the topography and surface roughness. The phases of the crystalline structures were identified through micro-Raman spectroscopy (MRS). After that, a veneering ceramic was applied to all Y-TZP surfaces and subjected to shear bond strength (SBS) testing at a speed of 0,5mm/min until fracture. Failure modes were classified as adhesive, cohesive, or mixed. SBS results were subjected to one-way ANOVA ( = 0.05) followed by Tukeys test ( = 0.05). Results. No differences were shown between groups regarding surface roughness (p=0,255), although Confocal and AFM images showed topographical differences among groups. The LC group showed the highest SBS median values, which were significantly different from S70 and JOX (p=0,008), which were not different. S40 showed the lowest SBS median values (15,43 MPa). All specimens exhibited typical Y-TZP tetragonal bands and monoclinic phases. Most specimens of all groups exhibited mixed failures (67,5%) and the remaining specimens exhibited adhesive failures. Conclusion. Additional surface treatments for Y-TZP, sandblasting, and 70 % power sonochemical treatment showed similar results but did not increase SBS to a feldspathic ceramic.